Analisis Effect Size Pengaruh Bahan Ajar Fisika dan IPA Terpadu Terhadap Hasil Belajar Siswa - Hanum, Siti Asma; Asrizal, Asrizal; Festiyed, Festiyed (Jurnal Penelitian Pembelajaran Fisika, 2021)
The 21st century is developing rapidly, marked by advances in science and technology, causing the world to enter the era of the industrial revolution 4.0. The industrial revolution 4.0 is an era that views information technology as the foundation of human life. The development of digital technology has disrupted various human activities, including the fields of science and technology and the arts, and education is no exception. This type of research is a journal review with effect size analysis. The real condition found in the field is the low learning outcomes of students due to a lack of learning resources such as teaching materials. One solution to overcome this problem is to use teaching materials in the learning process. Journal review is a study by reviewing and analyzing research data from several existing research results. The journal review stage with the effect size analysis, namely conducting literature reviews, data collection, review and assessment of articles, analysis and interpretation of articles and preparation of report results. From the results of the calculated data analysis, the research results were obtained. First, the use of Integrated Physics and Science teaching materials has a very significant effect on the education level of high school and junior high school. Second, the use of Integrated Physics and Science teaching materials has a very significant effect in terms of material for high school and junior high school. Third, the use of teaching materials has a very significant effect in terms of its integration.